Non‐histaminergic angioedema: focus on bradykinin‐mediated angioedema. Issue 4 (21st March 2013) - Busse, P. J.; Buckland, M. S.
Summary Angioedema is a result of increased vascular permeability, with subsequent extravasation of intravascular fluid into the surrounding tissues. Angioedema may be mediated by histamine, bradykinin or other mediators. Histaminergic angioedema generally presents with urticaria and/or pruritus and will respond to conventional treatment with antihistamines, corticosteroids or epinephrine. Bradykinin‐mediated angioedema, which includes hereditary angioedema (HAE types I, II and III), acquired C1‐INH deficiency, and angiotensin‐converting enzyme inhibitor‐induced angioedema does not typically present with urticaria/weals and does not respond to conventional agents such as antihistamines or corticosteroids. In recent years, several agents that prevent the generation or activity of bradykinin have been developed for the treatment of HAE types I and II and are also being evaluated in other types of bradykinin‐mediated angioedema. These agents have the potential to improve outcomes for patients with different forms of bradykinin‐mediated angioedema.